Qualitative Properties of Solutions of Second-Order Neutral Differential Equations - Omar Bazighifan (Symmetry, 2020)
In this work, we consider a type of second-order functional differential equations and establish qualitative properties of their solutions. These new results complement and improve a number of results reported in the literature. Finally, we provide an example that illustrates our results.